PENERAPAN PELAYANAN HOLISTIK GEREJA DALAM KEBHINNEKAAN UMAT BERAGAMA DI INDONESIA - Eddy Danukusumah; Lusyana Yosepha Winata; Rikardo P. Sianipar (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
This study aims to provide an understanding of the church's responsibility for holistic service in society, nation and state and to create a harmonious life so that the unity and integrity of Indonesia can be maintained. Republik Indonesia is the largest archipelagic country in the world with more than 17,000 islands. Through its uniqueness and diversity, Indonesia is known as a country with pluralistic society. This can be seen in the Indonesian value